Use of sederal cultures as a renewable energy source in organic agriculture - Горб, О. О.; Чайка, Т. О.; Яснолоб, І. О. (Scientific Progress & Innovations, 2017)
The article substantiates the importance of using organic crops in organic farming. The peculiarities of their use for certain crops are highlighted. The advantages of using green fertilizers and suggestions for their use by farms and farmers have been proved. Sederal cultures in vegetable growing and their agrotechnological features are presented. The forms of fodder production and application of green fertilizers are substantiated. The climatic, soil, organizational and economic conditions of use of sederal cultures are presented.